2019
DOI: 10.1007/s11060-019-03184-1
|View full text |Cite
|
Sign up to set email alerts
|

Gliosarcoma: distinct molecular pathways and genomic alterations identified by DNA copy number/SNP microarray analysis

Abstract: Purpose Gliosarcoma is a histologic variant of glioblastoma (GBM), and like GBM carries a poor prognosis. Median survival is less than one (1) year with less than 5% of patients alive after 5 years. Although there is no cure, standard treatment includes surgery, radiation and chemotherapy. While very similar to GBM, gliosarcoma exhibits several distinct differences, morphologically and molecularly. Therefore, we report a comprehensive analysis of DNA copy number changes in gliosarcoma using a cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…Our PGS cohort was also demographically and clinically comparable with previous described cases of GS (37,39,49), patients were predominantly middle-aged men (M:F ratio 19:7, median age 59.7) with a tumor located in the temporal lobe (57.7%). Also, in concordance with GS being a variant of GBM, IDH-wildtype, and prior reported genetic alterations (50,51) all PGS tumors were IDH1-wildtype.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our PGS cohort was also demographically and clinically comparable with previous described cases of GS (37,39,49), patients were predominantly middle-aged men (M:F ratio 19:7, median age 59.7) with a tumor located in the temporal lobe (57.7%). Also, in concordance with GS being a variant of GBM, IDH-wildtype, and prior reported genetic alterations (50,51) all PGS tumors were IDH1-wildtype.…”
Section: Discussionsupporting
confidence: 78%
“…It was recently proposed that the GS diagnosis could be estimated by preoperatively imaging analysis (27), but this is conflicted by a study finding a slightly larger area of edema to be the only distinct feature of GS compared to conventional GBM tumors upon evaluation of the radiological VASARI feature set (51). Radiological analysis of our PGS patients revealed that 58% had a peripheral tumor abutting dura, consistent with previous reported imaging characteristics (28)(29)(30)(31).…”
Section: Discussionsupporting
confidence: 58%
“…Histologically, gliosarcomas can be distinguished by the biphasic presence of both glial and sarcomatous components (2)(3)(4). Molecular studies on gliosarcoma have suggested a monoclonal origin of these distinct cell populations prior to their divergent differentiation patterns based on the presence of shared somatic alterations, including that of tumor suppressors TP53 and PTEN (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the giant cell GBM have outcomes similar to classical GBM. In gliosarcoma, TP53 mutations are rare, and EGFR amplification is also uncommon, and contains CDKN2A deletion (Lowder et al, 2019). The clinical outcome of gliosarcoma differs from classical GBM, but there are still conflicting and uncertain results from various studies.…”
Section: Idh-wild Type and Idh-mutation Typementioning
confidence: 99%